2021
DOI: 10.1029/2020jg005938
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Data Reveal Contrasting Sources for Carbon Fractions in Thermokarst Lakes and Rivers of Eastern Canada (Nunavik, Quebec)

Abstract: Warming-induced permafrost thaw enables the transport of large stocks of previously frozen soil organic carbon through aquatic systems as dissolved organic carbon (DOC) and particulate organic carbon (POC), and its subsequent microbial mineralization to methane (CH 4 ) and carbon dioxide (CO 2 ) (Kling et al., 1991;Schuur et al., 2015). Permafrost-derived CH 4 and CO 2 represent a net input of carbon to the atmosphere and a positive feedback to climate change, but there is a large uncertainty on the extent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 69 publications
(189 reference statements)
1
7
0
Order By: Relevance
“…The radiocarbon age of DOC in the water (~ 3800 yr BP) was much older than DIC in the water column and the CO 2 and CH 4 in the bubbles, which is in line with previous peatland thaw lake studies (Gonzalez Moguel et al 2021). The 14 C–DOC age of the lake water closely resembles reported ages of DOC in the pore waters of nearby peat plateau active layers (Tanentzap et al 2021) and had a terrigenous stable carbon isotope (𝛿 13 C) value of −26.9‰ (Karlsson et al 2003), suggesting allochthonous origins.…”
Section: Discussionsupporting
confidence: 90%
“…The radiocarbon age of DOC in the water (~ 3800 yr BP) was much older than DIC in the water column and the CO 2 and CH 4 in the bubbles, which is in line with previous peatland thaw lake studies (Gonzalez Moguel et al 2021). The 14 C–DOC age of the lake water closely resembles reported ages of DOC in the pore waters of nearby peat plateau active layers (Tanentzap et al 2021) and had a terrigenous stable carbon isotope (𝛿 13 C) value of −26.9‰ (Karlsson et al 2003), suggesting allochthonous origins.…”
Section: Discussionsupporting
confidence: 90%
“…The SAS valley contains permafrost peatlands, and peatlands in general have higher DOC export and concentrations than mineral soils ( Dillon and Molot, 1997 ). Radiocarbon analysis of DOC in the SAS River during winter has indicated much older carbon than in nearby non-peatland rivers, and thermokarst lakes in the KWK River watershed ( Gonzalez Moguel et al, 2021 ), suggesting the mobilization of old frozen peat deposits. In a study of streams flowing through discontinuous permafrost, higher concentrations of DON, as well as higher DOC and lower DOC quality, were associated with a greater extent of permafrost in the watershed ( Balcarczyk et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the third bacterial group correlated with salinity, Gammaproteobacteria, we identified the OM43 clade, a methylotroph in the Methylophilaceae family (Giovannoni et al, 2008), and the SAR92 clade (family Porticoccaceae), which possess genes for the degradation of complex polysaccharides (Klindworth et al, 2014). These two clades are common in coastal waters (RappĂ© et al, 1997;Morris et al, 2006;Stingl et al, 2007), and a culture study has shown that their growth is stimulated by high molecular weight organic matter (Sosa et al, 2015).…”
Section: Salinity Effectsmentioning
confidence: 97%
“…Several studies have used the natural abundance of radiocarbon ( 14 C) to estimate the contribution of permafrost carbon to lake carbon cycling (Zimov et al 1997, Nakagawa et al 2002, Walter et al 2006, Elder et al 2018, Gonzalez Moguel et al 2021. However, most studies focused on thermokarst systems overlying degrading Yedoma deposits, Pleistocene-aged permafrost soils with high ice and organic carbon content, in northern Alaska and Siberia (Matveev et al 2016, Walter Anthony et al 2018, Elder et al 2019, Dean et al 2020, Estop-AragonĂ©s et al 2020, Kuhn et al 2023.…”
Section: Introductionmentioning
confidence: 99%